PENGARUH KEADILAN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PT. MUARA MALL TERNATE) - Albaar, Arsyila Humairah; Kamis, Ruslan (Jurnal Manajemen Sinergi, 2022)
This study aims to determine the effect of 1) To find out whether organizational justice has an effect on employee turnover intention at PT Muara Mall Ternate; (2) Knowing whether organizational justice has an effect on job satisfaction at PT Muara Mall Ternate; (3) Knowing whether job satisfaction has an effect on employee turnover intention at PT Muara Mall Ternate; and (4) Knowing whether organizational justice has an effect on turnover intention with job satisfaction as a mediating variable at PT Muara Mall Ternate. The number of research samples is 71 respondents. The data analysis technique used in this study is SEM analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool. Methodology: The analytical model used are Structural Equation Modeling with SMART PLS as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 71 employee. Finding: H1, H2, H3, and H4 are accepted at the 5% confidence level. n other words, the t-count value of each variable is greater than the ttable at the 5% confidence level. Conclusion: Te results of this study indicate that: (1) Organizational justice has a positive and positive effect on turnover intention at PT. Muara Mall Ternate; (2) organizational justice has a positive influence on job satisfaction at PT. Muara Mall Ternate; (3) Job satisfaction has a positive influence on turnover intention at PT. Muara Mall Ternate; and (4) and job satisfaction is a variable capable of mediating the effect of organizational justice on turnover intention at PT. Muara Mall Ternate